I toponimi nei dizionari bilingui italiano-polacco, polacco-italiano in un contesto diacronico di apprendimento - Palmarini, Luca (Studia Romanica Posnaniensia, 2020)
The purpose of this is to analyze the toponyms present in some Italian-Polish and Polish-Italian bilingual dictionaries. After selecting a “skeleton” of the dictionaries that trace part of the history of the bilingual lexicography in question, we move on to the analysis of the toponyms used in the dictionaries. In a lexicultural context, understood as the transfer of the cultural elements of a given language, we observe the choices made by lexicographers of the different eras and try to understand the reasons, sometimes of a personal nature or dictated by the historical context, or sometimes influenced by the political system in a given country. At the same time, we want to highlight the evolution in the diachronic field that toponyms and their equivalents have had in the dictionaries in question, as well as their value in teaching a particular foreign language.